Internal Extractive Electrospray Ionization Mass Spectrometry for Quantitative Determination of Fluoroquinolones Captured by Magnetic Molecularly Imprinted Polymers from Raw Milk. Issue 1 (December 2017) - Zhang, Hua; Kou, Wei; Bibi, Aisha; Jia, Qiong; Su, Rui; Chen, Huanwen; Huang, Keke
Abstract Antibiotics contamination in food products is of increasing concern due to their potential threat on human health. Herein solid-phase extraction based on magnetic molecularly imprinted polymers coupled with internal extractive electrospray ionization mass spectrometry (MMIPs-SPE-iEESI-MS) was designed for the quantitative analysis of trace fluoroquinolones (FQs) in raw milk samples. FQs in the raw milk sample (2 mL) were selectively captured by the easily-lab-made magnetic molecularly imprinted polymers (MMIPs), and then directly eluted by 100 µ L electrospraying solvent biased with +3.0 kV to produce protonated FQs ions for mass spectrometric characterization. Satisfactory analytical performance was obtained in the quantitative analysis of three kinds of FQs (i .e ., norfloxacin, enoxacin, and fleroxacin). For all the samples tested, the established method showed a low limit of detection (LOD ≤ 0.03 µ g L−1 ) and a high analysis speed (≤4 min per sample). The analytical performance for real sample analysis was validated by a nationally standardized protocol using LC-MS, resulting in acceptable relative error values from −5.8% to +6.9% for 6 tested samples. Our results demonstrate that MMIPs-SPE-iEESI-MS is a new strategy for the quantitative analysis of FQs in complex biological mixtures such as raw milk, showing promising applications in food safety control and biofluid sample analysis.